Dismantle the body, build new senses: An analysis of poetic works between Brazil and Argentina - Rafaela Scardino (Estudios de Teoría Literaria)
The books Mugido [ou diário de uma doula], by the Brazilian poet Marília Floôr Kosby, and Carneada, by the Argentine poet Soledad Castresana, accept the coexistence with both the indeterminacy of life that begins and the inevitability of death, without shying away from questioning our participation in systems of reductionism and expropriation. The reflection proposed here seeks to establish a dialogue between the two mentioned poetry collections and the research of Donna Haraway (2022), Vinciane Despret (2018), as well as other authors, who point to horizons for a good living and a dignified dying, calling us to disarticulation, in a communication always unforeseen, yet rich in meanings.